Self-Disclosure Counsel in Revealing Psychological Problems (Study On Online Counseling Service Counselives) - Ratasya Deranti; Sarwani Sarwani (Universitas Lambung Mangkurat, 2024)
People with psychological problems generally find it difficult to express themselves and have poor communication skills. This research focuses on the counselor's self-disclosure in revealing his psychological problems in online counseling services. The research used a qualitative approach with descriptive research type. Data collection techniques using interviews, observation, documentation, and literature study. This research uses the concept of self-disclosure as well as the theory of the Johari Window and Communication Privacy Management. The results showed that the main factors that influence the counselee's self-disclosure are listeners and channels. The counselee's trust in the listener and the response given by the listener is the counselee's consideration. The channel factor in the form of a disinhibition effect affects the counselor's self-disclosure in online counseling services. The supporting factors for self-disclosure were found, namely the topic. The reasons for the counselor's self-disclosure include the tendency of dangerous psychological problems, physical pain, complaints, emotional support, asking for help, and psychological control. The counselor tends to get positive effects from self-disclosure such as catharsis, self-knowledge, and self-acceptance. The effects felt different for each individual, a negative effect was found in the form of vulnerability.